A composite index-based insurance instrument for managing the financial risk of variable hydrometeorology for electric utilities - Yash Amonkar; Corey Pahel-Short; Amir Zeighami; Yufei Su; Jordan D Kern; Gregory W Characklis (Environmental Research: Energy, 2025)
Variable hydrometeorological conditions can impact electric utilities’ financial stability. Extreme temperatures often increase electricity demand, raising utility costs, while drought reduces hydropower generation and often reduces revenues, with financial impacts potentially exacerbated by spikes in fuel prices, particularly natural gas. In this study, a model of the US. West Coast power system is combined with a financial risk model of a large California electric utility as it responds to variable hydrometeorology and market conditions, and is used to test the performance of a novel financial tool for managing risk. An insurance contract based on a composite index of measures related to streamflow, temperature, and natural gas prices is developed and its cost-effectiveness is compared against a portfolio of three currently available index contracts each based on a single index. The new composite index contract achieves an equivalent reduction in the utility’s net revenue variance as a portfolio of the three existing contract types for roughly half the cost with the cost reduction largely attributable to lower basis risk associated with the composite index contract. The utility’s financial risk and the effectiveness of the new contract are also explored under an alternative regulatory scenario involving a pollution tax intended to reduce air pollution damages and emissions. Overall, this case study represents a new approach to managing financial risk arising from hydrometeorological and market variability for vertically integrated utilities, the most common utility structure.